Urgensi Ketersediaan Ruang Terbuka Hijau sebagai Ruang Publik dalam Tata Kota Berwawasan Lingkungan Hidup - F.C. Susila Adiyanta (Gema Keadilan, 2018)
The development of urban areas carried out by the government and the private sector as an activity can affect and bring impacts on the environment and the surrounding environment. The trend of increasing urbanization in urban areas in various cities in Indonesia, including Semarang as an urban destination, generally raises various problems, the lack of availability of various service facilities for primary community life needs, especially residential issues and other public facilities, namely various facilities transportation, decreasing the quality of the urban environment and the ineffectiveness and efficiency of the land and space used plan regulation. Departing from the reality of the above problems, the focus of the study in this article is what is the urgency of the availability of public green open spaces in sustainable urban spatial planning.The results of the research on the topics raised in this article are briefly formulated, namely: a) Availability of public space and green open space (RTH) is an integral and inseparable part of urban spatial planning; b) Public spaces and urban green spaces have a main and strategic function for the social interaction of urban communities, the heart of the balance of ecosystems and the environment of the city, and as a manifestation of social, economic, cultural values and actualization of the face of urban life; and c) Sustainable management, designation and utilization of public space and green open space can be carried out optimally from synergies between city government, the private sector and the community. Recommendations from this study are: a) Realization of management, designation, and utilization of public spaces and green and sustainable open spaces can be done formally and informally by the city government with the support of the private sector and the community. b) Policies and arrangements for urban area development must be based on a plan for sustainable urban spatial planning and attention to environmental aspects in addition to economic and social aspects; c) to be able to realize the functions and designation of public spaces and green open spaces whose concessions and sustainability are in accordance with the development plan and urban spatial planning, it is necessary to enforce the law and impose strict and severe sanctions on all parties who violate the law.